Direct access valve‐in‐valve implantation for management of complex valvulopathy. Issue 7 (8th April 2019) - Kossar, Alexander P.; Borger, Michael; George, Isaac
Abstract: The management of bioprosthetic structural valve degeneration requires complex surgical or transcatheter re‐intervention for which many high‐risk patients are not considered candidates. Here, we describe a technique for a direct surgical access valve‐in‐valve implantation in patients with complex bioprosthetic valvulopathy for whom standard surgical valve replacement and percutaneous interventions were high‐risk and contraindicated, respectively.